Molecular Modelling of Broccoli Myrosinase and Its Interaction with Different Ligands - Castillo-Nara, A; Mahn-Osses, A; Roman-Aliste, J; Cottet-Bustamante, L (Italian Association of Chemical Engineering - AIDIC, 2018)
Myrosinase (ß-thioglucosidase glucohydrolase (EC 3.2.3.1)) is a glycoprotein responsible for the hydrolysis of glucosinolates, a group of sulfur-containing secondary metabolites present in Brassicaceae plants. Sulforaphane, a powerful anti-cancer compound, comes from the hydrolysis of glucoraphanin, the main glucosinolate found in broccoli. The aim of this work was to investigate the interaction between broccoli myrosinase and different substrates through molecular modelling. Currently the amino acid sequence and the molecular structure of broccoli myrosinase are unknown. The amino acid sequence was deduced from the nucleotide sequence, which in turn was obtained experimentally. The primary sequence of broccoli myrosinase used for modelling consisted of 548 amino acids. The three-dimensional model was generated by an ab initio/threading method using the crystal structure of 1MYR_A and 1DWF_M of Sinapis alba, 1CBG_A of Trifolium repens L, 3PTK_A of Oryza sativa and 3WQ4_A of Camellia sinensis as templates, employing the I-TASSER server. The interaction with glucoraphanin (GRA), sinigrin (SIN), glucoiberin (GIB) and N-acetylglucosamine (NAG) was investigated through molecular docking. The binding energy of GRA, SIN, GIB and NAG to myrosinase were -3.80; -4.71; -4.77 and -5.55 (Kcal/mol), respectively. The simulations of the interaction between GRA and myrosinase suggested that the residues of the active site responsible for substrate stabilization by hydrogen bonding were Gln207, Gly431, Ser433 and Trp 477. The residue involved in the hydrolysis of the ß-D-thioglucose binding was Tyr352. NAG interacts with the active site, as inhibitor. Our results will allow further studies about molecular mechanisms of broccoli myrosinase. Copyright © 2018, AIDIC Servizi S.r.l.